ANALISIS KELAYAKAN USAHATANI UBI JALAR (Ipomoea batatas L.) VARIETAS CILEMBU DI DESA KEPUNDUNG KECAMATAN REBAN KABUPATEN BATANG - Laili Chasanah; Lutfi Aris Sasongko; Renan Subantoro (MEDIAGRO, 2018)
This Research aims to know the revenue level, and the feasibility level of Cilembu Varieties Sweet Potato Farming in terms of BEP and R/C. The basic method used is descriptive. Determination of location sample is done purposively. The data used are primary and secondary data. The data was collected by interview, recording and observation. The respondents in this study were 25 farmers. Based on research the total cost is Rp.1,423,483/planting season (for 0.1-0.15 ha land area), Rp.2,761,542/planting season (for 0.2-0.25 ha land area) and Rp.6,278,958/planting season (for 0.3–0.5 ha). Total costs consist of equipment depreciation costs, tax cost, tractor cost of fertilizer costs, pesticide costs, female labor costs, male labor costs, transport cost and sack costs. While revenue is Rp.1,535.000/planting season (for 0.1–0.15 ha), Rp.3,768,571/planting season (for 0.2–0.25 ha), Rp.8,666,667 planting season (for 0.3-0.5 ha). Based on the calculation, it is known that the average return sweet potato farm is Rp.111,518/planting season (for 0,1–0,15 ha), Rp.1,007,030/planting season (for 0.2–0.25 ha) and Rp.2,387,708/planting season (for 0.3–0.5 ha). BEP value of production quantity is equal to 1,311 kg/planting season (for 0.1–0.15 ha), 2,099 kg/planting season (for 0,2–0,25 ha) and 6,279 kg/planting season (for 0.3– 0.5 ha. While Break Even Point on price is Rp.1,079/kg (for 0.1–0.15 ha), Rp.1,179/kg (for 0.2–0.5 ha) and Rp.752/kg (for 0.3–0.5 ha). Based on the analysis of the R/C with a value of 1.07 for land area 0.1-0.5 ha, 1.36 for 0.2-0.25 ha land area and 0.38 for 0.3-0.5 ha.Keywords: Sweet Potato, Revenue, Return, BEP, R/C